Adapting To Change: A PEST Analysis Of Private Universities In Palembang In The Era Of Digital Transformation - Irayani Makmun; Mariyam Zanariah; Lusia Nargis; Amrillah Azrin; Muhammad Ridwan (UNIVED Press, 2025)
The rapid progress of digital technologies has significantly altered higher education, forcing institutions to adjust to emerging political, economic, social, and technological (PEST) realities. Private universities in Palembang, Indonesia, encounter distinct challenges and opportunities during this digital transformation, yet there is a lack of comprehensive research that systematically explores the external factors affecting their adaptation strategies. This research utilizes a PEST analysis framework to examine the influence of political regulations, economic limitations, societal changes, and technological progress on private universities in Palembang as they strive to manage digital transformation. Using a qualitative methodology, this study integrates secondary data from government initiatives, institutional reports, and scholarly literature, along with firsthand insights from university stakeholders. This study aims to provide insights into how these institutions can adapt to changes in their external environment. The results indicate that political variables, such as national education strategies and accreditation requirements, play a crucial role in influencing the adoption of digital technologies, while financial obstacles like funding constraints and student affordability impede technological investments. Societal factors, including evolving student expectations and gaps in digital literacy, also affect institutional approaches, whereas differences in technological infrastructure create both challenges and avenues for innovation. Through a comprehensive PEST analysis, this study adds to the conversation on the resilience of higher education and provides practical recommendations for policymakers, university administrators, and educators within Indonesia's changing digital environment.